Jewish Education in Algerian Jewish Communities—Multiple Identities in an Era of Change (1830–1939) - Charvit, Yossef (Religions, 2024)
Our discussion of the Algerian Jewish community’s Jewish education during the French period (1830–1939) sheds light on the community’s multiplicity of identities viewed through the prism of the Spanish diaspora and French colonialism and sociology. Algerian Jewry’s multiple identities during the French period originate in the community’s education, both general and Jewish. The Jewish education in Algeria fueled loyalty to one’s Jewish identity and heritage and partially knit together the fissures that materialized in Jewish society ever more forcefully in this era of change. This article proposes a new methodological and historiographical approach based upon the examination of diverse sources—from communal and colonial sources to rabbinic, consular, and scholarly ones—using them to present a complete and multidimensional historical picture. Recognizing the many identities adopted by Algerian Jews during the French period is indispensable to conducting balanced and quality research into Algerian Jewry’s history. The complexity of Algerian Jews’ identity during the French period was the source of its richness and amplitude and a point of contention in the historiographical research of Algerian Jewish history.